Envolvimento da via da quinurenina na retirada do etanol: evidências comportamentais e bioquímicas - Santos, Luana Carla dos (2020)
Anxiety and depression are symptoms associated with ethanol withdrawal that lead individuals to relapse. In the tryptophan pathway, the enzyme indoleamine 2,3 dioxygenase (IDO) is responsible for converting tryptophan to kynurenine. Deregulation of this pathway is associated with psychiatric disorders, including anxiety and depression. The present study tested the hypothesis that the kynurenine pathway participates in modulating the behavioral effects caused by short- and long-term ethanol withdrawal. In experiment 1, Wistar rats received increasing ethanol concentrations for 21 days and were subjected to a battery of behavioral tests 3, 5, 10, 19, and 21 days after ethanol removal. In experiment 2, the animals were subjected to the same ethanol exposure protocol, euthanized 3 days (short term) or 21 days (long term) after ethanol removal. The brains were dissected to analyze the concentration of kynurenine (as a measure of IDO activity) in the prefrontal cortex, hippocampus, and striatum. In experiment 3, rats were subjected to behavioral tests on days 3, 19, and 21 after removing ethanol, and the brains were dissected for analysis of IDO activity in the areas mentioned above. Short-term ethanol withdrawal decreased the exploration of open arms in the elevated plus-maze. In contrast, in the forced swim test, rats subjected to long-term withdrawal showed a longer immobility time than control animals. The removal of ethanol did not alter the rats' locomotion or motor coordination (experiment 1). In experiment 2, the long-term withdrawal of ethanol increased the concentrations of kynurenine in the prefrontal cortex. In females, the administration of minocycline prevented the anxiogenic-like behavior promoted by the short-term ethanol withdrawal. This drug also prevented the effect of the long-term withdrawal on depressive-like behaviors. There was no locomotor alteration, neither in the concentrations of kynurenine in females (experiment 3). In conclusion, short-term ethanol withdrawal favored anxious behavior, while long-term withdrawal-induced depressive behavior. Prolonged ethanol withdrawal raised kynurenine levels, specifically in the prefrontal cortex in males, suggesting that the depressive responses observed after prolonged withdrawal may be related to increased IDO activity. In females, the administration of minocycline was able to reverse anxious and depressive behaviors caused by the withdrawal of ethanol, reinforcing that this pathway may be an option in the pharmacotherapy of ethanol withdrawal.